Study of the Cancellation of the Deed of Sale and Purchase Agreement By the Court of ConsequencesAct against the law (Case Study of Decision Number 55/Pdt.G/2022/Pn.Dpk) - Arifin, Ajun; Samosir, Tetti (Dinasti Research, 2025)
The Sales and Purchase Agreement (PPJB) is a crucial legal instrument in property transactions in Indonesia, but its cancellation by the court creates significant legal complexity for legal certainty and investor protection. This study analyzes the court's legal considerations in canceling a PPJB deed due to unlawful acts through a case study of Decision Number 55/Pdt.G/2022/PN.DPK which was upheld at the cassation level, using normative juridical methods and a descriptive analytical approach to examine the consistency of the application of contract law and the effectiveness of legal protection for land title holders. The research findings show a fundamental inconsistency in the court's decision, which declared the plaintiff a good-faith buyer in the conventional case, but in the counter-conventional case, declared the plaintiff to have committed a breach of contract with disproportionate sanctions in the form of cancellation of the agreement and loss of payment of Rp. 2,320,000,000. This contradiction indicates a systemic weakness in distinguishing the concepts of default and unlawful acts, a disregard for the principle of proportionality of sanctions, and the ineffectiveness of available legal protection mechanisms because the land registration system can be canceled based on inconsistent considerations. This study concludes the need for reformulation of the judicial approach in handling PPJB disputes through the development of a consistent, proportional, and just legal framework to maintain public trust in the legal system and support a healthy and sustainable property investment climate.